Social Capital as a Local Wisdom of Farmer in Managing Agricultural Resources in Lubuk Pakam Sub-district, Deli Serdang District - Sihar Pandapotan (Budapest International Research and Critics University, 2019)
This study will relate to the concept of sustainable development where the emphasis is not only on economic growth alone, but on socio-cultural factors that lead to the wise use of the environment. This research traces various forms of local wisdom as social capital for paddy rice farmers in Deli SerdangDistrict. Besides as a form of preserving the environment wisely. But also as one of the solutions in solving human and environmental problems. This study uses a qualitative research method with a descriptive approach. This method and approach was chosen because in carrying out the documentation it is necessary to have a holistic description of a study. The results showed that paddy rice farmers in Deli SerdangDistrict had combined forms of local wisdom with technological advancements as social capital in managing agricultural resources. This is shown in the process of farming that still uses traditional methods but is also supported by modern farming tools. In general, the form of local wisdom is demonstrated through the revitalization of mutual cooperation values, growing the collectivity of farmers, and the implementation of simple rituals as a form of gratitude. Therefore, the preservation of various forms of local wisdom with a global perspective is one of the social capital and references in improving the quality of farmer’slife in particular, and the development of Indonesian agriculture in general.